Consequences' function on the alteration of pilot brands hierarchies (2010)
Consequences' function on the alteration of brands hierarchies (positioning) was examined from an operant perspective of symbolic behavior. Brands memory, preference, and purchase intention were compared between experimental and control groups. Experimental group received training, with informative consequences, of six functionally equivalent classes of stimuli. Control group was exposed to a similar procedure, without informative consequences. It was found that informative consequences were positively associated with alteration in memory, preference, and purchase intention hierarchies, unlike from the absence of such consequences. It also discusses the consequences' role in formation as well as in derived hierarchies alteration.